2020
DOI: 10.1097/ncq.0000000000000537
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Prone Positioning for COVID-19 Patients Outside the Intensive Care Unit

Abstract: Background: Proning intubated intensive care unit patients for the management of acute respiratory distress syndrome is an accepted standard of practice. We examined the nursing climate in 4 units and its impact on implementing a novel self-proning protocol to treat COVID-19 patients outside the intensive care unit. Local Problem: Nursing units previously designated for medical/surgical populations had to adjust quickly to provide evidence-based care fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…Similar to our research, in 1 report, PT team members provided quality, focused interactions, support, and tools needed to successfully perform the intervention. 29 , 30 No other studies were found that used a multidisciplinary approach to proning.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our research, in 1 report, PT team members provided quality, focused interactions, support, and tools needed to successfully perform the intervention. 29 , 30 No other studies were found that used a multidisciplinary approach to proning.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in nursing attitudes about the benefits proning are documented in a separate article which shows significant variation between units. 38 This underlines a need for more uniform and ongoing education to promote awareness among both nurses and physicians.…”
Section: Discussionmentioning
confidence: 99%
“…March 2020 data from the Jiangsu Province in China demonstrated lower mortality and decreased intubation rates with and ventilation is improved. [4][5][6]16 PP may also facilitate postural drainage and secretion clearance. 6 Given combined benefits and improved oxygenation, engaging patients in APP serves as a low-risk intervention, supporting the management of patients on the medical floor while helping reduce the risk of intubation.…”
Section: App For Patients With Covid-19mentioning
confidence: 99%
“…[4][5][6]16 PP may also facilitate postural drainage and secretion clearance. 6 Given combined benefits and improved oxygenation, engaging patients in APP serves as a low-risk intervention, supporting the management of patients on the medical floor while helping reduce the risk of intubation. [4][5][6]17 In May 2020, nonventilated patients with COVID-19 ARDS were admitted to a designated 22-bed acute care medical unit at a 596-bed Level I trauma center and community teaching hospital in southcentral Pennsylvania.…”
Section: App For Patients With Covid-19mentioning
confidence: 99%
See 1 more Smart Citation